PEMBELAJARAN E-LEARNING BERBASIS EDMODO DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Diana Kuji Kalinggoru; Desak Nyoman Budiningsih; Ida Bagus Ari Arjaya (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
Edmodo is an educational application with a facebook-like social media platform that can be used in learning. In general, teachers rarely use information-based learning, communication and technology, and only focus on learning by using Liquid Crystal Display (LCD) alone without utilizing the maximum technology applications for educational purposes. The purpose of this research is to analyze the difference of critical thinking ability between learners which applied E-Learning learning based on Edmodo without Contextual Teaching and Learning (CTL) approach with students who applied E-Learning learning based on Edmodo with Contextual Teaching and Learning approach CTL). This type of research is Quasi Experimental Design with Nonequivalent Control Group Design research conducted at SMA (SLUA) ​​Saraswati 1 Denpasar from February to April. The sample in this research is the students of class X MIA 5 as control class and class X MIA 1 as experiment class. Critical thinking ability is measured using essay test by using rubric of critical thinking ability of learners. The results obtained by using One Way ONOVA test show that there is a significant difference from the application of Edmodo based E-Learning learning with CTL approach to students' critical thinking ability (p = 0,05). The conclusion of this research is the application of Edmodo based E-learning learning with CTL approach better than Edmodo based E-learning learning without CTL approach to the critical thinking ability of learners.